Pola Manajemen Kurikulum Berbasis Islam Terpadu di SD Islam Terpadu Menara Fitrah Kabupaten Ogan Ilir - Syamilah, Izzah (Program Pascasarjana UNU Surakarta, 2024)
This research aims to 1) analyze the management pattern of the Integrated Islamic curriculum at the Menara Fitrah Integrated Islamic Elementary School; and 2) Strategy for implementing the school curriculum according to the characteristics of the Integrated Islamic School Network (JSIT). Qualitative descriptive is this type of research. The Menara Fitrah Integrated Islamic Elementary School, Ogan Ilir Regency was the place where the research was conducted because the Menara Fitrah Integrated Islamic Elementary School has implemented an Integrated Islamic curriculum. The subjects of this research include school principals and curriculum coordinators. The methods used to collect data include interviews, observation, and documentation studies. Data triangulation is used as a method of data validity in this research. The interactive model from Miles, Huberman & Saldana is a data analysis technique used which includes data reduction, data presentation, and conclusion. Based on research findings, show: 1) Menara Fitrah Integrated Islamic Elementary School manages an Integrated Islamic-based school curriculum by applying management principles which include planning, implementation, and control/evaluation; 2) The strategy implemented by the Menara Fitrah Integrated Islamic Elementary School in managing the curriculum to suit the characteristics of JSIT is to recruit teachers who have certain abilities and facilitate teachers with training that supports and strengthens communication and collaboration between school stakeholders.